Carboxyl Terminus of Hsp70-Interacting Protein Is Increased in Serum and Cerebrospinal Fluid of Patients With Spinocerebellar Ataxia Type 3 - Hu, Zheng-wei; Yang, Zhi-hua; Zhang, Shuo; Liu, Yu-tao; Yang, Jing; Wang, Yan-lin; Mao, Cheng-yuan; Zhang, Qi-meng; Shi, Chang-he; Xu, Yu-ming (Frontiers in Neurology, 2019)
Background: Spinocerebellar ataxia type 3 (SCA3)/Machado-Joseph disease (MJD) is the most common type of autosomal dominant ataxia. Like other neurodegenerative diseases, is characterized by the dysfunction of the protein quality control (PQC) system. The carboxyl terminus of the Hsp70-interacting protein (CHIP), an important component of PQC, participates in the clearance of misfolded proteins to maintain cellular homeostasis. While no cure for SCA3 exists, the disease progresses slowly. Thus, the identification of biomarkers that indicate the severity and prognosis of this disease would be valuable. Methods: In this exploratory case-control study, we quantitatively evaluated the concentrations of CHIP in the sera of 80 patients with SCA3 and 80 age and sex-matched controls, using the enzyme-linked immunosorbent assay (ELISA). CHIP levels in the cerebrospinal fluid (CSF) donated by six patients and six healthy volunteers, who were matched for sex and age were also measured. All the baseline data were collected, and the patients underwent clinical evaluation. The correlations between CHIP levels and several clinical measurements were analyzed. Results: The serum CHIP level in the SCA3 group was (80.93 ± 28.68) ng/mL, which was significantly higher than those in the control group [(40.37 ± 18.55) ng/mL]. Similar results were observed for the CSF [(164.59 ± 42.99) ng/mL and (37.47 ± 7.85) ng/mL, respectively]. CSF CHIP levels were significantly higher than the serum CHIP levels in the SCA3 group. but not in the control group. The Bonferroni correction for Kruskal-Wallis test revealed no significant difference between the serum and CSF of the patients and the control group. Multivariate linear regression showed that serum CHIP levels correlated positively with disease severity, as measured by the Scale for the Assessment and Rating of Ataxia (SARA) and the International Cooperative Ataxia Rating Scale (ICARS). Moreover, we found that serum CHIP levels were moderately correlated with age in healthy controls. Conclusion: The present study determined that CHIP levels increased significantly in the serum and CSF of patients with SCA3 and that serum CHIP levels were corelated with disease severity. Thus, CHIP is a promising biomarker for SCA3.